Citizen engagement with information when adapting to health crises: four distinctive profiles - Kortesalmi, Marilla; Jalonen, Harri; Kallunki, Valdemar R. V. (Emerald, 2026)
Purpose This study examines citizens' engagement with information during the COVID-19 crisis. While the desire for information intensifies during health crises, such circumstances pose challenges to citizens' ability of to adapt to new situations. Familiar information behaviour, such as seeking and scanning intertwine with collective sensemaking to navigate the situation successfully. While citizen-led adaptation is crucial in public crisis management, limited academic attention has focused on understanding the process of information engagement. The purpose of the study is to investigate how information behaviour and collective sensemaking jointly support adaptation from public management viewpoint. Design/methodology/approach The data for this study were provided by 30 semi-structured interviews with members of COVID-19-related Facebook groups. All participants were from Finland, which provided the context for the study. Abductive thematic analysis and narrative practices were applied to analyse the interviews. Findings The findings revealed that while citizens' information engagement shared patterns, it manifested in distinctive ways in terms of information behaviours and epistemic ideals. We assign four profiles to encapsulate the narratives elicited: Attendants, Mainstreamers, Outriders and Tribesmen. Originality/value This article contributes to the discourse on citizens' information behaviour and sensemaking in informal environments. By focusing on citizens' viewpoints concerning adaptation in times of crisis, the findings contribute to the literature on public crisis management in societal emergencies.
Keywords: Public crisis management; Citizen information engagement; Collective sensemaking; Health crisis; COVID-19; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|